Encoding and Decoding of Secret Messages Using Matrices - James, Niwagaba (Kabale University, 2022)
A Dissertation Submitted to the Faculty of Education in Partial Fulfilment of the Requirements for the Award of the Bachelor's Degree of Science with Education at Kabale University